PROFIL PENGGUNAAN DAN INFORMASI PEMANFAATAN KHASIAT PRODUK HERBAL PADA TERAPI DEGENENRATIF DI TOKO “X” KOTA CILACAP - Setia Permana, Denih Agus (Gamma Publishing, 2023)
Herbal medicine has been widely known for both curing disease and maintaining body health. Treatment of degenerative diseases still relies on therapy that uses synthetic drugs which are used in the long term, thereby increasing the risk of side effects. The increasing use of herbal medicines in society is because it is believed that herbal medicines have fewer side effects than synthetic medicines. Herbal medicines are available in various dosage forms, the aim of this research is to determine the use of herbal medicines used in the therapy of degenerative diseases at the